Retinoic Acid Signaling Plays a Crucial Role in Excessive Caffeine Intake-Disturbed Apoptosis and Differentiation of Myogenic Progenitors - Wu, Nian; Li, Yingshi; He, Xiangyue; Lin, Jiayi; Long, Denglu; Cheng, Xin; Brand-Saberi, Beate; Wang, Guang; Yang, Xuesong (Frontiers in Cell and Developmental Biology, 2021)
Whether or not the process of somitogenesis and myogenesis is affected by excessive caffeine intake still remains ambiguous. In this study, we first showed that caffeine treatment results in chest wall deformities and simultaneously reduced mRNA expressions of genes involved in myogenesis in the developing chicken embryos. We then used embryo cultures to assess in further detail how caffeine exposure affects the earliest steps of myogenesis, and demonstrated the caffeine treatment suppressed somitogenesis of chicken embryos by interfering with the expressions of crucial genes modulating apoptosis, proliferation and differentiation of myogenic progenitors in differentiating somites. These phenotypes were abrogated by an RA-antagonist in embryo cultures, even at low caffeine doses in C2C12 cells, implying that excess RA levels are responsible for these phenotypes in cells, and possibly in vivo. These findings highlight that excessive caffeine exposure is negatively involved in regulating the development of myogenic progenitors through interfering with RA signaling. The RA-somitogenesis/myogenesis pathway might be directly impacted by caffeine signaling, rather than reflecting an indirect effect of the toxicity of excess caffeine dosage.